Alcohol Consumption After Listing for Liver Transplantation Is Associated With Increased Risk of Alcohol Consumption After Transplantation - Léa Abrial; Domitille Erard; Laure Tron; Sylvie Radenne; Agnès Bonadona; Justine Barthelon; Térésa Antonini; Marie Noelle Hilleret; Thomas Decaens; Jérôme Dumortier; Charlotte Costentin (International Journal of Hepatology, 2025)
Conclusion: Alcohol consumption on the list was documented in 9.6% of the patients, associated with an increased risk of alcohol consumption after LT. These results support systematic screening of alcohol consumption and active addiction counseling before transplant. Importantly, 5-year overall survival since listing was not statistically different between patients with or without DAC during the waiting time period.